The role of DAND5 in the coordination of hiPSC-derived cardiomyocyte environmental cues: their impact on cardiomyocyte electrophysiology - Nunes, Mafalda dos Santos Marques (2022)
Tese de mestrado, Biologia Evolutiva e do Desenvolvimento, Universidade de Lisboa, Faculdade de Ciências, 2022